UPAYA MENINGKATKAN PEMAHAMAN SISWA TERHADAP ISI BACAAN MELALUI PENERAPAN MODEL PEMBELAJARAN TEORI SKEMATA PADA PEMBELAJARAN BAHASA INDONESIA DI KELAS VIII-4 SMP NEGERI 2 KUTALIMBARU TAHUN AJARAN 2018/2019 - Friska Siahaan (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2020)
This study aims to determine the increase in students' understanding of the reading content using the Schemata Theory learning model in Class VIII-4 of SMP Negeri 2 Kutalimbaru in the 2018/2019 academic year. The research method is in the form of classroom action research and the research subject is Class VIII-4. The class studied consisted of 36 students. Based on the learning outcomes of the first cycle, an average value of 75 was obtained. After the second cycle, there was an increase to 85. In this study, data on individual and classical learning completeness criteria were obtained, to as many as 36 students or 100%. Thus, the learning in this study can be said to be complete. The level of student mastery of the material being taught, which is made based on the final test, is 100% of students who have very high mastery. Based on the results of the research above, it can be concluded that learning using the Schemata Theory learning model in Class VIII-4 of SMP Negeri 2 Kutalimbaru in the 2018/2019 academic year experienced an increase in student understanding of the reading content.